2015
DOI: 10.5194/tc-9-957-2015
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of surface velocities and ice discharge of Larsen B outlet glaciers from 1995 to 2013

Abstract: Abstract. We use repeat-pass SAR data to produce detailed maps of surface motion covering the glaciers draining into the former Larsen B Ice Shelf, Antarctic Peninsula, for different epochs between 1995 and 2013. We combine the velocity maps with estimates of ice thickness to analyze fluctuations of ice discharge. The collapse of the central and northern sections of the ice shelf in 2002 led to a near-immediate acceleration of tributary glaciers as well as of the remnant ice shelf in Scar Inlet. Velocities of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 30 publications
6
88
4
Order By: Relevance
“…This corresponds well to observations of an immediate impact on the stress field through rift formation and acceleration of Scar Inlet, and a smaller and delayed signal in observed surface velocities for its tributary glaciers [Wuite et al, 2015]. The work of Khazendar et al [2015] has shown that the limited response of Leppard and Flask Glaciers is likely related to a reduction in buttressing by the Scar Inlet.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…This corresponds well to observations of an immediate impact on the stress field through rift formation and acceleration of Scar Inlet, and a smaller and delayed signal in observed surface velocities for its tributary glaciers [Wuite et al, 2015]. The work of Khazendar et al [2015] has shown that the limited response of Leppard and Flask Glaciers is likely related to a reduction in buttressing by the Scar Inlet.…”
Section: Discussionmentioning
confidence: 72%
“…This justifies the application of an instantaneous ice front perturbation in the model. The earliest observations of glacier velocities after the collapse date from December 2003, i.e., less than 2 years after the event [Wuite et al, 2015]. During this period, Hektoria and Green Glaciers increased their center line speed from about 365 m a −1 at the 1995 grounding line to more than 2000 m a −1 (or a sixfold increase) in 2003, while the grounding line retreated by several kilometers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations